PENGARUH LABA AKUNTANSI DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM DENGAN RISIKO PERUSAHAAN SEBAGAI VARIABEL INTERVIENING PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS KOMPAS 100 PERIODE 2011-2015 - Aerlangga Aerlangga (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2019)
This study aims to determine the effect of accounting earnings and firm size on stock returns with company risk as an intervening variable. The sampling method used was purposive sampling, from the population of companies in the kompas index 100 period 2011-2015, several samples will be selected based on certain criteria. This study has a characteristic that is by measuring accounting profit and company size by regressing each variable with company risk and also measuring accounting profit and company size and company risk by regressing each variable with stock returns so that the sensitivity values of each variable will be generated. The research data was tested by classical assumptions by using multiple regression analysis techniques using spss 22 for windows.The results showed that accounting profit partially affects the company's risk, the size of the company has a significant influence on company risk, accounting profit does not have a significant effect on stock returns, firm size does not have a significant effect on company size. The test is based on a confidence level of 95%, and an error rate of 5%.